Morphological and genetic variation among Phytophthora nicotianae var. nicotianae isolates causing fruit rot of bell pepper and their correlation with genetic variability among host genotypes - and BHAWNA SAXENA, S.K GUPTA*, KUMUD JARIAL, M.S. SAHARAN, R. KAUR (Indian Phytopathology, 2012)
Twenty three isolates of Phytophthora nicotianae var. nicotianae causing fruit rot of bell pepper (Capsicum annuum L.), collected from different locations of North India were used to study variability at morphological / genetic level. Variation among isolates was observed in mycelial colour, appearance, size and shape of sporangia. Oospore production with variable size was recorded only in ten isolates. Genetic variation was also studied with twenty four 10-mer oligonucleotide RAPD primers, out of which 14 primers yielded informative, strong and reproducible DNA amplicons of P. nicotianae var. nicotianae. The dendrogram produced from computerized cluster analysis of the DNA fingerprints revealed a great deal of heterogeneity among isolates. Seven bell pepper germplasm lines were also screened against these 23 isolates. Bell paper genotypes, Dark Green was found to be tolerant to 16 isolates while Feroz and Danish Wonder were tolerant to 14 isolates. Molecular markers viz., RAPD revealed genetic variation among fruit rot resistant and susceptible lines of bell pepper. Out of 23 primers used, polymorphism was observed with ten primers only. The similarity coefficient ranged from 0.59 to 0.77 indicating variability in the genotypes studied. Fruit rot tolerant lines viz., Feroz, Danish Wonder and Dark Green clustered in one group. Such lines can be used in developing fruit rot resistant varieties/hybrids to broad range of isolates.